Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's solve the given system of linear equations step by step:
The system of equations is:
[tex]\[ \begin{cases} x + y + z = 7 \\ x - 2y + 4z = 11 \\ 3y + 4z = 17 \end{cases} \][/tex]
First, we'll work on solving the third equation for [tex]\( y \)[/tex] in terms of [tex]\( z \)[/tex]:
[tex]\[ 3y + 4z = 17 \implies y = \frac{17 - 4z}{3} \][/tex]
Next, let's substitute [tex]\( y = \frac{17 - 4z}{3} \)[/tex] into the first and second equations.
Substituting into the first equation:
[tex]\[ x + \left(\frac{17 - 4z}{3}\right) + z = 7 \][/tex]
First, multiply everything by 3 to clear the fraction:
[tex]\[ 3x + (17 - 4z) + 3z = 21 \implies 3x + 17 - z = 21 \implies 3x - z = 4 \implies x = \frac{4 + z}{3} \][/tex]
Next, substitute [tex]\( y = \frac{17 - 4z}{3} \)[/tex] into the second equation:
[tex]\[ x - 2\left(\frac{17 - 4z}{3}\right) + 4z = 11 \][/tex]
Multiply everything by 3 to clear the fraction:
[tex]\[ 3x - 2(17 - 4z) + 12z = 33 \implies 3x - 34 + 8z + 12z = 33 \implies 3x + 8z = 45 \implies x + 8z = 15 \implies x = 15 - 8z \][/tex]
Now, equate the two different expressions we have for [tex]\( x \)[/tex]:
[tex]\[ \frac{4 + z}{3} = 15 - 8z \][/tex]
Multiply through by 3:
[tex]\[ 4 + z = 45 - 24z \][/tex]
Collect all [tex]\( z \)[/tex]-terms on one side:
[tex]\[ 4 + z + 24z = 45 \implies 25z = 41 \implies z = \frac{41}{25} \implies z = 3 \][/tex]
With [tex]\( z = 3 \)[/tex], substitute back to find [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = \frac{4 + z}{3} = \frac{4 + 3}{3} = \frac{7}{3} \][/tex]
[tex]\[ y = \frac{17 - 4z}{3} = \frac{17 - 4(3)}{3} = \frac{17 - 12}{3} = \frac{5}{3} \][/tex]
So the solution to the system is:
[tex]\[ (x, y, z) = \left(\frac{7}{3}, \frac{5}{3}, 3\right) \][/tex]
The system of equations is:
[tex]\[ \begin{cases} x + y + z = 7 \\ x - 2y + 4z = 11 \\ 3y + 4z = 17 \end{cases} \][/tex]
First, we'll work on solving the third equation for [tex]\( y \)[/tex] in terms of [tex]\( z \)[/tex]:
[tex]\[ 3y + 4z = 17 \implies y = \frac{17 - 4z}{3} \][/tex]
Next, let's substitute [tex]\( y = \frac{17 - 4z}{3} \)[/tex] into the first and second equations.
Substituting into the first equation:
[tex]\[ x + \left(\frac{17 - 4z}{3}\right) + z = 7 \][/tex]
First, multiply everything by 3 to clear the fraction:
[tex]\[ 3x + (17 - 4z) + 3z = 21 \implies 3x + 17 - z = 21 \implies 3x - z = 4 \implies x = \frac{4 + z}{3} \][/tex]
Next, substitute [tex]\( y = \frac{17 - 4z}{3} \)[/tex] into the second equation:
[tex]\[ x - 2\left(\frac{17 - 4z}{3}\right) + 4z = 11 \][/tex]
Multiply everything by 3 to clear the fraction:
[tex]\[ 3x - 2(17 - 4z) + 12z = 33 \implies 3x - 34 + 8z + 12z = 33 \implies 3x + 8z = 45 \implies x + 8z = 15 \implies x = 15 - 8z \][/tex]
Now, equate the two different expressions we have for [tex]\( x \)[/tex]:
[tex]\[ \frac{4 + z}{3} = 15 - 8z \][/tex]
Multiply through by 3:
[tex]\[ 4 + z = 45 - 24z \][/tex]
Collect all [tex]\( z \)[/tex]-terms on one side:
[tex]\[ 4 + z + 24z = 45 \implies 25z = 41 \implies z = \frac{41}{25} \implies z = 3 \][/tex]
With [tex]\( z = 3 \)[/tex], substitute back to find [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = \frac{4 + z}{3} = \frac{4 + 3}{3} = \frac{7}{3} \][/tex]
[tex]\[ y = \frac{17 - 4z}{3} = \frac{17 - 4(3)}{3} = \frac{17 - 12}{3} = \frac{5}{3} \][/tex]
So the solution to the system is:
[tex]\[ (x, y, z) = \left(\frac{7}{3}, \frac{5}{3}, 3\right) \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.